Assessment of Self-Contamination During Removal of Personal Protective Equipment for Ebola Patient Care. (1st August 2016) - Casanova, Lisa M.; Teal, Lisa J.; Sickbert-Bennett, Emily E.; Anderson, Deverick J.; Sexton, Daniel J.; Rutala, William A.; Weber, David J.
Abstract : OBJECTIVE: Ebola virus disease (EVD) places healthcare personnel (HCP) at high risk for infection during patient care, and personal protective equipment (PPE) is critical. Protocols for EVD PPE doffing have not been validated for prevention of viral self-contamination. Using surrogate viruses (non-enveloped MS2 and enveloped Φ6), we assessed self-contamination of skin and clothes when trained HCP doffed EVD PPE using a standardized protocol. METHODS: A total of 15 HCP donned EVD PPE for this study. Virus was applied to PPE, and a trained monitor guided them through the doffing protocol. Of the 15 participants, 10 used alcohol-based hand rub (ABHR) for glove and hand hygiene and 5 used hypochlorite for glove hygiene and ABHR for hand hygiene. Inner gloves, hands, face, and scrubs were sampled after doffing. RESULTS: After doffing, MS2 virus was detected on the inner glove worn on the dominant hand for 8 of 15 participants, on the non-dominant inner glove for 6 of 15 participants, and on scrubs for 2 of 15 participants. All MS2 on inner gloves was observed when ABHR was used for glove hygiene; none was observed when hypochlorite was used. When using hypochlorite for glove hygiene, 1 participant had MS2 on hands, and 1 had MS2 on scrubs. CONCLUSIONS: A structured doffing protocol using a trained monitor and ABHR protects against enveloped virus self-contamination. Non-enveloped virus (MS2) contamination was detected on inner gloves, possibly due to higher resistance to ABHR. Doffing protocols protective against all viruses need to incorporate highly effective glove and hand hygiene agents. Infect Control Hosp Epidemiol 2016;1–6